1997
DOI: 10.1515/jpme.1997.25.1.63
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of fetal cerebral vasodilatation induced by submaximal maternal dynamic exercise in human pregnancy

Abstract: To investigate the relationship between maternal exercise and fetal circulatory responses in humans during the third trimester of pregnancy, changes in uterine, umbilical and fetal cerebral circulations were measured by pulsed-Doppler ultrasound method in 14 healthy volunteer pregnant women before and just after a moderate non-exhaustive exercise. Maternal heart rate increased significantly reaching 80% of the theoretical maximal heart rate (TMHR) while uterine resistance indices did not change. The fetal hear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
8
0
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 21 publications
1
8
0
4
Order By: Relevance
“…A few studies found no change in FHR during or immediately after a maternal exercise session (Marsal et al 1979;Artal et al 1995;Bonnin et al 1997). Some studies found a few cases of decreased FHR immediately after a single session of maternal exercise (Jovanovic et al 1985;Watson et al 1991;Manders et al 1997).…”
Section: Fetal Hr and Hrv: Acute Responsementioning
confidence: 99%
See 1 more Smart Citation
“…A few studies found no change in FHR during or immediately after a maternal exercise session (Marsal et al 1979;Artal et al 1995;Bonnin et al 1997). Some studies found a few cases of decreased FHR immediately after a single session of maternal exercise (Jovanovic et al 1985;Watson et al 1991;Manders et al 1997).…”
Section: Fetal Hr and Hrv: Acute Responsementioning
confidence: 99%
“…While power in defined frequency bands cannot be used as a proxy for cardiac output, the finding is intriguing and warrants further investigation. Further, fetal internal carotid artery mean velocity increased and fetal cerebral resistance index decreased suggesting vasodilation (Bonnin et al 1997). The evidence overwhelmingly shows that maternal exercise does not have adverse fetal cardiovascular effects (Kennelly et al 2002b).…”
Section: Other Fetal Heart Measuresmentioning
confidence: 99%
“…They did not observe significant exercise-induced changes in umbilical perfusion,47 913 or even improvements due to decreased vascular resistance were reported 8. Two studies suggested fetal cerebral vasodilatation with maternal exercise 4 13. More discrepancies exist on the acute response of fetal HR (FHR) to late-pregnancy maternal exercise.…”
mentioning
confidence: 99%
“…Several studies evaluated the effects of a single bout of dynamic, submaximal exercise (usually, cycle-ergometry at ≤80% age-predicted maximum heart rate (HR max )) on the vascular resistance of the umbilical313 or fetal cerebral circulation in non-athletic, healthy women during the last trimester of uncomplicated pregnancy 4 13. They did not observe significant exercise-induced changes in umbilical perfusion,47 913 or even improvements due to decreased vascular resistance were reported 8.…”
mentioning
confidence: 99%
See 1 more Smart Citation